2012
DOI: 10.1590/s0101-28002012000200003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de diabetes mellitus em pacientes renais crônicos sob hemodiálise em Porto Alegre, Brasil

Abstract: The prevalence of DM among chronic HD patients in Porto Alegre is higher than what was previously published as a cause of CRF in the country, which indicates the possibility that this etiology of CRF may have been underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…With regard to the prevalence of DM among ESKD patients, the national scenario was illustrated by the 2012 Brazilian Chronic Dialysis Census, 5 revealing that 28.5% of patients on dialysis treatment also have diabetes as an associated comorbidity, which is a slightly lower figure than was found in the present study (33.10%). A study conducted in 2009 in the South of Brazil by Burmeister et al 15 reported that 37.9% of the hemodialysis patients studied also had DM. These epidemiological data suggest that there are significant regional differences in DM rates among hemodialysis patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…With regard to the prevalence of DM among ESKD patients, the national scenario was illustrated by the 2012 Brazilian Chronic Dialysis Census, 5 revealing that 28.5% of patients on dialysis treatment also have diabetes as an associated comorbidity, which is a slightly lower figure than was found in the present study (33.10%). A study conducted in 2009 in the South of Brazil by Burmeister et al 15 reported that 37.9% of the hemodialysis patients studied also had DM. These epidemiological data suggest that there are significant regional differences in DM rates among hemodialysis patients.…”
Section: Discussionmentioning
confidence: 97%
“…5 However, it should be acknowledged that DM associated with ESKD has been becoming increasingly predominant within the Brazilian epidemiological profile and if the trend continues it will reach worldwide prevalence rates in the next few years. 14,15 Considering the increasing role of diabetes mellitus as a cause of ESKD in our country, and the challenges involved in constructing AVFs in certain groups of patients, the primary objective of this study was to compare the mean duration of patency of occluded AVFs before this event, and the survival rates of arteriovenous fistulas constructed in patients with diabetes mellitus, with the same outcomes in patients who do not have diabetes mellitus, in patients given hemodialysis treatment at the Hospital Santa Casa de Misericórdia de Ponta Grossa (Parana, Brazil).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, diabetes, recognized as a socioeconomic disease, is considered one of the main causes for the appearance of kidney diseases in developed countries. Diabetic nephropathy is the main cause of CKD in the world and can lead to death 3 , 4 , 25 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the presence of DM, it is highlighted that it is the main cause of ARF, because persistent hyperglycemia causes damage to nephrons, leading to a diabetic nephropathy condition and reverberating on renal function failure; thus, the use of contrast presents a high risk of evolving to ARF and even death. Patients with DM require attention when performing procedures with contrast, needing evaluation of the renal function in order to minimize severe renal damage [36].…”
Section: Discussionmentioning
confidence: 99%